Investigating spatial skills and math anxiety as mediatorsinasequential mediation model: A pilot study - Wang, Lu (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2021)
Prior research showed a gender effect on spatial ability, math anxiety, andmath achievement. Lacking, however, is a comprehensive studythattested the mediation effects of spatial ability and math anxiety betweengender and math achievement in a sequential mediation model. Tofill thisgap, this pilot study tested two mediation relationships, one withspatial ability as a mediator, gender as a predictor, and math anxietyasanoutcome variable; the other with math anxiety as a mediator, spatial ability as a predictor, and math achievement as an outcome variable. Inaddition, the study tested the relative strengths of the relationshipbetween specific spatial skills that included perspective-taking, spatial imagery, and mental rotation and collegiate math achievement thatincluded trigonometry, calculus, and linear algebra) via canonical correlations. Lastly, gender differences in spatial skills, math anxiety, andmath achievement were investigated. The results of the independent t-tests showed that none of the well-documented gender differencesinspatial ability was found. Canonical correlation analysis showedthat asingle canonical variable is sufficient in accounting for math-spatial relationship. The sequential mediation model, with spatial abilityandmath achievement serving as the mediators in the model, fittedreasonably well. However, none of the mediation effects was statisticallysignificant. Implications of these findings and future directions of thisresearch are discussed.